An Exploratory Case Study of Mental Toughness Variability and Potential Influencers over 30 Days - Ken Bradford Cooper; Mark Wilson; Martin Ian Jones (MDPI AG, 2019)
The purpose of this study was to explore whether mental toughness varies across a 30-day training block and whether such variability is associated with specific antecedents. This exploratory case study research investigated mental toughness variability using the Mental Toughness Index (MTI) with thirteen elite master runners across a series of self-selected training sessions, followed by interviews and follow-up questionnaires, to identify primary influencers of variability. There were significant differences in the MTI scores between baseline (before the training period), and the minimum and the maximum reported score over five self-selected training sessions (p’s < 0.004). The proceeding follow-up interviews and questionnaires then provided insights into factors influencing this intra-individual variability. These higher-level themes included foundational wellbeing, specific preparation, and actions utilized in the moment. This study is the first to demonstrate within-person MTI variability across specific training sessions and provides initial insights for both athletes and practitioners into potential influencers of mental toughness.